Efficacy of a fixed combination of permethrin 54.5% and fipronil 6.1% (Effitix®) in dogs experimentally infested with Ixodes ricinus - Stéphane Bonneau; Nadège Reymond; Sandeep Gupta; Christelle Navarro (Parasites & Vectors, 2015)
Abstract Background Ticks are the most important vectors of disease-causing pathogens in domestic animals and are considered to be second worldwide to mosquitoes as vectors of human diseases. In Europe, Ixodes ricinus, the sheep tick, plays an important role as companion animal parasite but is also the primary vector of medically important diseases such as tick-borne encephalitis and Lyme borreliosis. The present study was designed to evaluate the efficacy under laboratory conditions of a new fixed spot-on combination of fipronil and permethrin (Effitix®, Virbac) in treating and preventing tick infestations of Ixodes ricinus in dogs. Methods Twelve dogs were included in this randomized, controlled, blinded laboratory study. They were randomly allocated to two groups of six dogs each according to their pre-treatment live attached Ixodes ricinus tick count. On day 0, the dogs from Group 2 were treated with the recommended dose of Effitix®, the dogs from Group 1 remained untreated. On days −2, 7, 14, 21, 28 and 35, all dogs were infested with 50 (±4) viable unfed adult Ixodes ricinus (20 ± 2 males, 30 ± 2 females). Ticks were removed and counted at 48 ± 2 hours post product administration or tick infestations. Results Through the study, the tick attachment rates for the untreated group were greater than 25% demonstrating that adequate levels of infestation were reached on the control dogs. Based on both arithmetic and geometric means (AM and GM), Effitix® was deemed to be effective against Ixodes ricinus on days 2, 9, 16, 23, 30 and 37 with a percentage of efficacy of 98%, 100%, 100%, 100%, 93% and 95% respectively (AM). No clinical abnormalities were detected during the study. Conclusions The study has shown under laboratory conditions, that Effitix® is a safe and an effective combination to treat and protect dogs from Ixodes ricinus up to 37 days after administration. The high immediate efficacy of 98% evaluated at 48 hours post-treatment was particularly interesting, meaning that Effitix has a curative effect against ticks (Ixodes ricinus) and provides a rapid control of existing Ixodes ricinus infestation on a dog at the time of treatment.